Nasal nitric oxide in healthy Chinese children aged 6–18 years - Wu, Yufen; Zhang, Hao; Wang, Jinrong; Han, Yuling; Shi, Yongsheng; Zhang, Qiaoling; Shen, Li; Jiang, Haohua; Jia, Chunmei; Yu, Yanyan; Long, Zhen; Ji, Minghong; et al. (Frontiers in Pediatrics, 2023)
Objectives To obtain the normal values of fractional concentration of nasal nitric oxide in Chinese children aged 6-18 years, so as to provide reference for clinical diagnosis. Methods 2580 out of 3200 children (1359 males and 1221 females), whom were included from 12 centers around China were taken tests, their height and weight were also recorded. Data were used to analyze the normal range and influencing factors of fractional concentration of nasal nitric oxide values . Measurements Data was measured using the Nano Coulomb Breath Analyzer (Sunvou-CA2122, Wuxi, China), according to the American Thoracic Society/European Respiratory Society (ATS/ERS) recommendations. Main Results We calculated the normal range and prediction equation of fractional concentration of nasal nitric oxide values in Chinese children aged 6-18 years. Conclusions Sex and age were two significant predictors of FnNO values for Chinese children(aged 12-18 yrs). The mean FnNO values of Chinese aged 6-18 yrs was 454.5 ± 176.2ppb, and 95% of them were in the range of 134.5-844.0ppb. The prediction rule of FnNO values for Chinese children aged 6-11 yrs was: FnNO = 298.881 + 17.974 × age. And for children aged 12-18 yrs was: FnNO = 579.222-30.332 × (male = 0, female = 1) - 5.503 × age.